Usefulness of Interleukin-18 as a Diagnostic Biomarker to Differentiate Adult-Onset Still’s Disease With/Without Macrophage Activation Syndrome From Other Secondary Hemophagocytic Lymphohistiocytosis in Adults - Shiga, Toshihiko; Nozaki, Yuji; Tomita, Daisuke; Kishimoto, Kazuya; Hirooka, Yasuaki; Kinoshita, Koji; Funauchi, Masanori; Matsumura, Itaru (Frontiers in Immunology, 2021)
Interleukin (IL)-18 is markedly elevated in systemic inflammatory diseases that cause the 'cytokine storm' such as adult-onset Still's disease (AOSD) and hemophagocytic lymphohistiocytosis (HLH). The differences in IL-18 between AOSD and HLH, especially in adults, is uncertain. Macrophage activation syndrome (MAS), a form of secondary HLH, is a common complication of AOSD, and it is often difficult to differentiate cases of AOSD that include MAS from other secondary HLH because of their similarities in pathogenesis and clinical characteristics. In this case-control study, we investigated whether serum IL-18 levels could be a useful biomarker for the differential diagnosis of AOSD with or without MAS (AOSD group) and other secondary HLH in adults (adult HLH group). We enrolled 46 patients diagnosed with AOSD including nine patients with MAS (35 without MAS) and 31 patients in the adult HLH group, which excluded AOSD-associated MAS. The clinical features and laboratory data were compared between the AOSD and adult HLH groups. A logistic regression analysis was used to identify factors with high efficacy in differentiating the two groups, followed by a receiver operating characteristic (ROC) curve analysis to evaluate the differential diagnostic ability of IL-18. We analyzed the correlation between IL-18 and various laboratory parameters in the AOSD group. The AOSD group's serum IL-18 levels were significantly higher than those of the adult HLH group and were closely correlated with ferritin, soluble interleukin-2 receptor (sIL-2R), transaminases, and L-lactate dehydrogenase. Univariate and multivariate logistic regression analyses revealed that IL-18, sIL-2R, and 'arthralgia or arthritis' are independent factors useful in the differential diagnosis of AOSD from adult HLH. In the differential diagnosis of both groups, the area under the curve obtained from the ROC curve of IL-18 with a cutoff value of 18,550 pg/mL was 0.91 (95% confidence interval 0.83–1.00; sensitivity 90.3%, specificity 93.5%), and the differential diagnosis ability of IL-18 was superior to that of other laboratory data. IL-18 could be a useful biomarker for the differential diagnosis of AOSD and adult HLH.